Pemahaman Makna Harfiah dan Majazi dalam Bahasa Arab: Potret Kemampuan Siswa SMP Lubbul Labib - Muhammad Asror; Ainur Rofiq Sofa (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the ability of students at SMP Lubbul Labib in distinguishing between literal (ḥarfī) and figurative (majāzī) meanings in Arabic. Mastery of these meanings is essential for understanding Arabic texts, especially in religious and literary contexts. The research adopts a descriptive quantitative approach, utilizing multiple-choice and essay tests as instruments to measure students' comprehension levels. The results reveal that most students still face difficulties in identifying figurative meanings, particularly when they appear in literary or religious sentence contexts that require deeper interpretation. These findings highlight the need for more contextual teaching strategies and the reinforcement of interpretative exercises in Arabic texts. The study recommends the implementation of context-based learning approaches and the integration of figurative meaning materials into classroom activities in a more intensive and sustainable manner.